Pemanfaatan Lahan untuk Budikdamber dan Hidroponik Sebagai Upaya Pemenuhan Kebutuhan Pangan Keluarga Di Kelurahan Dupak - Dinda ayu pramesthi; Sri Muljaningsih; Mohammad Wahed (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
East Java is a metropolitan city that is densely populated and will increase from year to year. In here, a lot of land that is used as malls, offices, settlements, and so on which rarely has no trees and far from the greening. Unfortunately, the other least land has not optimally utilized. One way to maximize the space for Dupak residents is to cultivate catfish which is very effective because it does not require large areas of land as good land utilization for feed's needs. The first job activity is explain about the plan to the dupak's people, providing modules, tools and materials including fish seeds, vegetable seeds and fish pellets, and introducing the technique of cultivating fish in buckets (BUDIKDAMBER). Through the Kuliah Kerja Nyata (KKN) UPN Veteran East Java, the target to be achieved is that partner can ultilize the least land maximally with farm and vegetable's plant using the BUDIKDAMBER technique. This KKN activity is expected to produce articles in online media about the BUDIKDAMBER technique. The results felt by partners later were catfish harvests starting from 2-4 months of maintenance. Vegetable harvest starts from 2 weeks-4th month of maintenance. Therefore, the organic fish and vegetables hopefully can fulfill dupak's people daily needs, even for their new income later.